(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
The article examines the features of investment real estate accounting in Uzbekistan and the impact of the transition to international financial reporting standards, in particular IAS 40 "Investment Real Estate". The current problems of the national accounting system, such as the use of historical value and insufficient transparency of reporting for foreign investors, are analyzed. updating national standards, improving the skills of accountants, developing practical recommendations and modernizing accounting systems. The implementation of the proposed measures is aimed at increasing the investment attractiveness of Uzbekistan and ensuring sustainable economic growth.